2021
DOI: 10.1097/bpo.0000000000001742
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Coverage Decreases at the End of Skeletal Growth: A 3DCT Study of Healthy Hips

Abstract: Background: Abnormalities in size and position of the acetabulum have been linked to both developmental dysplasia of the hip and femoroacetabular impingement. Owing to its 3-dimensional (3D) complexity, plain radiography and cross-sectional studies [computed tomography (CT) and magnetic resonance imaging] have limitations in their ability to capture the complexity of the acetabular 3D anatomy. The goal of the study was to use 3D computed tomography reconstructions to identify the acetabular lunate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This study revealed that anteroposterior coverage was correlated with bony acetabular growth in childhood and that anterior coverage was particularly important for subsequent acetabular growth. Some etiological studies have shown that acetabular coverage decreases at the end of skeletal growth and that the acetabular version increases to reduce anterior coverage during adolescence 27,28. Thus, anterior coverage may be important only in early childhood for acetabular development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed that anteroposterior coverage was correlated with bony acetabular growth in childhood and that anterior coverage was particularly important for subsequent acetabular growth. Some etiological studies have shown that acetabular coverage decreases at the end of skeletal growth and that the acetabular version increases to reduce anterior coverage during adolescence 27,28. Thus, anterior coverage may be important only in early childhood for acetabular development.…”
Section: Discussionmentioning
confidence: 99%
“…Some etiological studies have shown that acetabular coverage decreases at the end of skeletal growth and that the acetabular version increases to reduce anterior coverage during adolescence. 27,28 Thus, anterior coverage may be important only in early childhood for acetabular development.…”
Section: Discussionmentioning
confidence: 99%